ECOTOURISM PLANNING ON THE RAPID-GROWING ECONOMIC AREA : A STUDY OF PACITAN, INDONESIA - Rita Parmawati; Heru Wiwoho Supadi Putra; Agung Sih Kurnianto (ASEAN Journal on Hospitality and Tourism, 2018)
Pacitan Regency has a tourist destination characterized by nature and the relationship between humans and nature. The purpose of this study is to identify the potential, problems, carrying capacity and constraints of ecotourism development, as well as develop management strategies in Pacitan. Observations and interviews were conducted to reveal information related to the research objectives. We do index on the components of ecotourism management that we have designed. SWOT analysis is used to determine and map the potential and problems of management and development of ecotourism. the total GRDP shows that the economy of the Pacitan Regency is characterized by the economy of the Tertiary Sector. On the IFAS, the potential of natural resources plays a very important strength (weight value 0.204) and on the weaknesses, accessibility and facilities and infrastructure plays a very important role (weighted values 0.153 and 0.130). On the EFAS, government policy support reaches the highest weight (0.135) on an opportunity, and on threat factors, security and object equality with other regions play a very important role  (0.106 and 0.105)